2005
DOI: 10.1002/pam.20088
|View full text |Cite
|
Sign up to set email alerts
|

Assessing evidence of environmental inequities: A meta-analysis

Abstract: Over the past decade activists, academics, and policymakers have devoted a great deal of attention to “environmental equity,” or the notion that sources of potential environmental risk may be concentrated among racial and ethnic minorities and the poor. Despite these efforts, the existence and extent of environmental inequities is still the subject of intense scholarly debate. This manuscript reports the results from a meta-analysis of 49 environmental equity studies. The analysis demonstrates that while there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
151
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(163 citation statements)
references
References 28 publications
9
151
3
Order By: Relevance
“…Some authors resort to intuition or theory to express their preferences for unit choices or predictions about the effects of the choice of spatial unit (e.g., Cutter and others 1996, McMaster and others 1997, Hockman and Morris 1998, Sui 1999, Bowen 2001, Mantaay 2002. Ringquist (2005) sees unit of analysis largely as a matter of aggregation bias associated with larger units of analysis, where injustice effects should appear stronger at lower resolution. On the other hand, Dolinoy and Miranda (2004) express the intuition that higher resolution predicts higher exposure concentrations.…”
Section: Maup and Ejmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors resort to intuition or theory to express their preferences for unit choices or predictions about the effects of the choice of spatial unit (e.g., Cutter and others 1996, McMaster and others 1997, Hockman and Morris 1998, Sui 1999, Bowen 2001, Mantaay 2002. Ringquist (2005) sees unit of analysis largely as a matter of aggregation bias associated with larger units of analysis, where injustice effects should appear stronger at lower resolution. On the other hand, Dolinoy and Miranda (2004) express the intuition that higher resolution predicts higher exposure concentrations.…”
Section: Maup and Ejmentioning
confidence: 99%
“…For examples of this research, see Anderton and others (1994), Glickman (1994, 2004, Bowen and others (1995), Cutter and others (1996), Sui (1999), Sheppard and others (1999), Taquino and others (2002), Dolinoy and Miranda (2004), and Baden and others (2007). In his meta-analysis of EJ studies, Ringquist (2005) identifies unit choice as a major source of contention in the literature; his analysis, however, finds little evidence of systematic aggregation bias. In total, even if the conventional wisdom is that effects get stronger as scale of aggregation increases, the empirical evidence on the matter is quite mixed.…”
Section: Maup and Ejmentioning
confidence: 99%
See 1 more Smart Citation
“…The discussion here is necessarily cursory because of the broader focus of this article and the availability of several comprehensive surveys (Bowen 2002, Pearce 2003, Hamilton 2005, and Ringquist 2005. Early studies, which focused mainly on air pollution in the United States, generally found a negative association between environmental risk and income (e.g., Freeman 1972, Zupan 1973, Asch and Seneca 1978, Harrison and Rubinfeld 1978.…”
Section: Resultsmentioning
confidence: 99%
“…In 1987, a study [26] of landfill sites across the US would find that zip codes with these hazardous sites had, on average, double the percent minority of zip codes without landfills. In a seminal meta-analysis of 49 environmental justice studies between 1995 and 2005, Ringquist [27] concluded that race-based environmental inequality was ubiquitous. Numerous subsequent case studies of urban environmental injustices have found that spatial distribution of pollution hazards and socially vulnerable populations (minority and low income) cluster together in Detroit [28], Los Angeles [29][30][31], New York City [32], Portland [33], St. Louis [34], and Tampa Bay [35].…”
Section: Environmental Inequities and Gentrificationmentioning
confidence: 99%